Anomalies in The Registration of Mortgage Rights on Residential Properties: A Legal Analysis of Delays In Title Transfers Within The Home Mortgage Ecosystem - Ruby W H Oktolina Samosir; Suyud Margono; Ari Tridianto; Robert L Simanungkalit (PALAR | PAKUAN LAW REVIEW, 2026)
This study examines legal issues in Indonesian property transactions arising from the absence of clear regulatory time limits for title transfer (balik nama) from developers to buyers. This legal gap creates a transitional period in which buyers have fulfilled their financial obligations but have not yet obtained legally registered property rights, resulting in legal uncertainty. The study aims to analyze the juridical implications of delayed title transfer on the validity of mortgage rights and the legal position of the parties involved, particularly in the event of developer bankruptcy. This research employs a normative juridical method using statutory and case approaches, focusing on relevant legislation and the Supreme Court Decision No. 2768 K/Pdt/2011. The findings reveal that delays in title transfer directly affect the registration of mortgage rights, which is constitutive in nature. Failure to comply with procedural requirements, particularly the statutory time limit for registration, may render the Mortgage Certificate legally defective and eliminate the creditor’s preferential rights. Consequently, creditors may be downgraded to concurrent status, while buyers face the risk of losing legal protection over the property, especially in bankruptcy proceedings. The study concludes that the absence of clear regulatory timelines creates systemic legal uncertainty affecting both consumers and financial institutions. Therefore, it is recommended that the government establish strict and enforceable deadlines for title transfer processes, accompanied by administrative sanctions for non-compliance, in order to ensure legal certainty, enhance consumer protection, and strengthen the integrity of the property and banking sectors.